Neonatal invasive fungal infection in England 2004–2010. (6th March 2014) - Oeser, C.; Vergnano, S.; Naidoo, R.; Anthony, M.; Chang, J.; Chow, P.; Clarke, P.; Embleton, N.; Kennea, N.; Pattnayak, S.; Reichert, B.; Scorrer, T.; et al.
Abstract Rates of invasive fungal infection are highest among neonates, especially those of low birthweight. This study aimed to describe the current epidemiology of invasive neonatal fungal infections in a UK neonatal infection surveillance network. From 2004 to 2010 prospective multicentre surveillance was conducted by 14 neonatal units using a web‐based database. Clinicians then completed a standardized pro forma for each positive fungal blood and/or cerebrospinal fluid culture. The overall incidence was 2.4/1000 neonatal unit admissions and was highest among babies <1000 g (extreme low birthweight, 18.8/1000). Only five infants (6%) were >1500 g. The majority of infections were caused by Candida albicans (59; 69%) and Candida parapsilosis (17; 20%); 33% of infants had received antifungal prophylaxis. Known risk factors (use of central venous catheter, parenteral nutrition, previous antibiotic use) were common among cases. The attributable case fatality rate was 21% (18/84). Extreme low birthweight infants remain at highest risk of invasive fungal infection and prophylaxis should be particularly considered for this group. The number needing to receive prophylaxis to prevent one case varies significantly among units, hence unit‐specific decisions are required. Further research is still needed into the optimal empiric and therapeutic strategies.